2008
DOI: 10.1097/brs.0b013e318182c347
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Treatment of Back Complaints on Children and Adolescents

Abstract: An individual assessment by a knowledgeable physiotherapist and an active treatment model improve how children and adolescents experience their back problems with respect to health and physical function, pain, strength, and mobility, regardless of whether treatment consists of a home exercise program with follow-up or home exercise combined with exercise and treatment supervised by a physiotherapist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 30 publications
4
64
0
2
Order By: Relevance
“…6,8,9 Three randomized control trials by Jones et al, 6 Ahlqwist et al, 7 and Fanucchi et al 8 explored the effectiveness of an exercise intervention for LBP in adolescents without spinal deformity. Jones et al 6 and Fanucchi et al 8 found significant between-group differences in pain intensity reduction, but Ahlqwist et al 7 did not.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…6,8,9 Three randomized control trials by Jones et al, 6 Ahlqwist et al, 7 and Fanucchi et al 8 explored the effectiveness of an exercise intervention for LBP in adolescents without spinal deformity. Jones et al 6 and Fanucchi et al 8 found significant between-group differences in pain intensity reduction, but Ahlqwist et al 7 did not.…”
Section: Introductionmentioning
confidence: 98%
“…5 Furthermore, adolescents with a previous history of LBP are at risk for developing LBP in the future. 6 Researchers have advocated properly treating LBP during adolescence to prevent recurrent episodes into adulthood, 7 but clinical practice guidelines for adolescents have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, children with an adequate hamstring extensibility seem to have a lower risk of pelvic/spinal postural disorders (de Lemos, dos Santos & Gaya, 2012;López-Miñarro & Alacid, 2010; Muyor, Alacid, Rodríguez-García, & López-Miñarro, 2012), current low back pain (Jones, Stratton, Reilly, & Unnithan, 2005;Roy, Shaw, & Beattie, 2015) and neck tension (Mikkelsson, et al, 2006), as well as a lower risk of low back pain later during adulthood (Hestbaek, Leboeuf-Yde, Kyvik, & Manniche, 2006). Additionally, in children with low back pain an improvement in their hamstring extensibility levels has also been associated to a reduction of their pain levels (Ahlqwist, Hagman, Kjellby-Wendt, & Beckung, 2008;Jones, Stratton, Reilly, & Unnithan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2). The most common criterion was 'motor, sensory or Toda et al 23 Ahlqwist et al 24 Childs et al 26 Katz et al 27 Brinkhaus et al 25 3. LBP and any leg pain but excluded those with motor, sensory or reflex changes…”
Section: Resultsmentioning
confidence: 99%
“…radicular pain, positive straight leg raise, with or without exclusion of those with motor, sensory or reflex changes). [23][24][25][26][27] Some studies only excluded patients when motor, reflex or sensory deficits were present. [28][29][30][31][32][33] Other studies did not appear to Figure 2 Criteria for exclusion of nerve root involvement (n550).…”
mentioning
confidence: 99%